2005
DOI: 10.1159/000084295
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Budesonide and the SH-Metabolite I of Erdosteine Acts Synergistically in Reducing Chemiluminescence during Human Neutrophil Respiratory Burst

Abstract: Activated neutrophils can release superoxide anion and nitric oxide (NO), which subsequently combine with each other to yield peroxynitrite anions, powerful and harmful oxidants that preferentially mediate the oxidation of the thiol groups in proteins and non-protein molecules. These oxidants play a direct role in the inflammatory process in chronic obstructive pulmonary disease and asthma by increasing the number of neutrophils and macrophages that induce a self-sustaining phlogogenic loop. Budesonide (BUD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 99 publications
1
18
0
Order By: Relevance
“…MPO enzyme of the neutrophils catalyzes the formation of such potent cytotoxic oxidants as HOCl from H 2 O 2 and chloride ions and N-chloramines. These oxidants play a direct role in the inflammatory process in chronic inflammatory processes by increasing the number of neutrophils and macrophages that induce a self-sustaining phlogogenic loop [35]. Infiltration of leukocytes into the mucosa has been suggested to contribute significantly to the tissue necrosis and mucosal dysfunction associated with colitis [34] because they are the producers of pro-inflammatory mediators and a major source of reactive oxygen radicals in the inflamed colon mucosa [36].…”
Section: Discussionmentioning
confidence: 99%
“…MPO enzyme of the neutrophils catalyzes the formation of such potent cytotoxic oxidants as HOCl from H 2 O 2 and chloride ions and N-chloramines. These oxidants play a direct role in the inflammatory process in chronic inflammatory processes by increasing the number of neutrophils and macrophages that induce a self-sustaining phlogogenic loop [35]. Infiltration of leukocytes into the mucosa has been suggested to contribute significantly to the tissue necrosis and mucosal dysfunction associated with colitis [34] because they are the producers of pro-inflammatory mediators and a major source of reactive oxygen radicals in the inflamed colon mucosa [36].…”
Section: Discussionmentioning
confidence: 99%
“…The role of neutrophils and oxidative damage in the lung after lower I/R injury is well documented [1,[24][25][26][27]. It was demonstrated that limb I/R injury could not only lead to increased vascular permeability in the skeletal muscle but in the lung as well [28].…”
Section: Discussionmentioning
confidence: 99%
“…Erdosteine is a muco-active drug which, after metabolization produces an active metabolite called Met I with sulfhydryl group. 25 We observed significant protective effect of erdosteine on oxidative stress in liver of rats during RCM-induced I/R injury because it is both active in reducing the release of superoxide anion, nitric oxide and peroxynitrite. 26,27 Yagmurca et al 28 demonstrated that erdosteine treatment against doxorubicin-induced hepatotoxicity improved increased TBARS level.…”
Section: Discussionmentioning
confidence: 73%
“…We observed significant protective effect of erdosteine on GSH levels in liver of RCM-induced I/R injury in rats because the metabolization of mucoactive drug erdosteine produces an active metabolite (Met I) with a reducing SH group. 25,35 In addition to its mucolytic action, Met I also is an useful antioxidant. 13 In current study, we showed histopathological changes such as cellular disruption, cell vacuolization and central necrosis in rats received RCM.…”
Section: Discussionmentioning
confidence: 99%